EFFECTS OF SIMPLIFIED CHEMICAL KINETIC MODEL ON THE MICRO-FLAME STRUCTURE AND TEMPERATURE OF THE LEAN PREMIXED METHANE-AIR MIXTURES - JUNJIE CHEN; XUHUI GAO (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The effect of simplified chemical kinetic model on the micro-flame structure, central axis and wall temperatures were investigated with different one-step global chemical kinetic mechanisms following Mantel, Duterque and Fernández-Tarrazo models. Numerical investigations of the premixed methane-air flame in the micro-channel and lean conditions were carried out to compare and analyze the effect of the comprehensive chemical kinetic mechanisms. The results indicate that one-step global chemical kinetic mechanism affects both the micro-flame shape and the combustion temperature. Among three simulation models, Mantel model allows a stable micro-flame with a bamboo shoot form, which anchor at the inlet. Duterque model gives a stable elongated micro-flame with a considerable ignition delay, and a dead zone with fluid accumulation is observed at the entrance, which may explain the very high combustion temperature and the fast reaction rate obtained, despite the micro-flame development presents a very hot spot and causes a broadening of the combustion zone. Fernández-Tarrazo model results in a rapid extinction and doesn't seem to take all the kinetic behavior into account for the appropriate micro-combustion simulations.